Understanding the mechanisms of mobile health apps acceptance among silver generation in China: a mediation and moderation analysis - Xie, Qing; Bali Mahomed, Anuar Shah; Mohamed, Rosmah; Subramaniam, Anusuiya (Human Resources Management Academic Research Society (HRMARS), 2024)
The rapid expansion of mobile technology has led to the integration of AI-enhanced chatbots as virtual assistants within mHealth apps, providing continuous support for users. However, variations in mHealth app design features influence user perceptions and acceptance intentions. This study aims to examine the mediation and moderation effects impacting the acceptance of mHealth apps among the silver generation (aged 55 and above) mobile users in China. The SOR Model explains the mediating role of initial trust, while VUT investigates the moderating roles of perceived anthropomorphism and perceived intelligence. Data was collected from 641 Chinese silver generation users with mobile phone experience in the past six months. The results indicated that initial trust mediates the influence of companion presence on mHealth app acceptance intention. Perceived anthropomorphism moderates the relationship between companion presence and mHealth acceptance intention. Perceived anthropomorphism also moderates the relationship between initial trust and mHealth acceptance intention. This study provides new insights into the mechanisms of mHealth app acceptance and offers substantial contributions for practitioners to improve app features.